Grape colored and flavored rice wine - Buno, Imee Margarethe Cezar
ABSTRACT The study aimed to develop colored and flavored rice wine. In Phase I of the study, flavored rice wine was developed by selecting the most acceptable PhilRice wine with added different fruit imitation flavors. Grape flavored rice wine was selected and described by 25 panelists in a consumer acceptability test as having moderately strong alcohol aroma and grape aftertaste. Rice aroma and taste was described as mild in the grape flavored rice wine. The other flavor attributes of the grape flavored rice wine was described as having slightly strong characteristic. Correlation analyses revealed that the specific descriptors that have positive contributions to the acceptability of the flavored rice wine were fruity, alcohol and sweet attributes. Bitter, sour and rice attributes gave negative contribution to the rating of the acceptability of the flavored rice wine. Appropriate color for grape flavored rice wine was established using light to dark shades of purple in Phase II of the study. The selected color for grape flavored rice wine was light purple which had a color measure of 10 PB 4/10 in the Munsell Book of Color. Microbiological examination for grape flavored and colored rice wine conducted in Phase III showed an average total plate count of <100 cfu/ml, yeast and mold count <10 cfu/ml and Lactobacilli count <10 cfu/ml rice wine. Grape colored and flavored rice wine had pH value 3.8, titratable acidity 3.7 ml of 0.1N NaOH/10 ml sample, total soluble solids 13.6°Bx, and alcohol content 14%. Rice wine is known to change its color and flavor through time. Further study on the determination of stability of grape colored and flavored rice wine at room and chilled temperature storage was recommended.